Broussonetia Papyrifera (Paper Mulberry) - Krrshnaswamy, V. S. (Indian Forester, 1957)
This note furnishes information regarding the distribution, climate and soil, and general characters of Broussonetia papyrifera, as also methods of regeneration, tending and management, various methods of utilization and statistical information about the same species. The possibilities of growing this species successfully in the moist types of forests in India, temperate and tropical, have also been indicated.